POST-WAR REVITALIZATION OF THE URBAN SPACE OF UKRAINE AS A NATURAL ECONOMIC SYSTEM AND THE FUTURE INNOVATIVE ENVIRONMENT - Tiutiunnyk, Hanna; Kupinets, Larysa (Collection of scientific papers «ΛΌГOΣ», 2022)
Revitalization and development of urban settlements in the context of their multifunctionality require a focus on the diversity of use of its territories, functional and social combination. The city is a changing reality that has undergone significant modifications throughout history. Sustainable development of Ukraine in the context of solving security issues should be the central idea of ​​economic transformations of post-war reconstruction. This is a powerful impetus and a future example of a brighter expression of power through the formation of a unique model of the country on the basis of sustainability, innovation, inclusiveness, creativity, through the implementation and improvement of positive world experience. The world experience of cities that have suffered great destruction, in the vast majority is characterized by the fact that after quite severe events, cities are rebuilt from scratch. This allows cities to become dynamic founders of innovative architecture.